THE NEED FOR 'RE-EDITING' GAMELYN' - Vázquez, Nila (International Journal of English Studies, 2009)
Moderin Philology aims at re-discovering old texts by renewing the approaches and techniques used in critical editing. In the present article, some arguments in favour of the 'need' for editing anew the Tale of tiamelyn (included in the manuscripts of Chaucer's Canterbury Tales) are presented. After an analysis of previous editions of this Tale, tlhe contents of a forilicoming edition of tiamelyn are outlined.